Implementation of Direct Marketing in Asset Lease of PT. Kereta Api Indonesia (Persero) by Non-Transportation Commercialization Unit (KNA) DAOP 6 Yogyakarta - Hidayat, Anas; Ardian (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
This study aims to analyze the application of direct marketing strategies in the leasing of non-transportation assets by PT Kereta Api Indonesia (Persero) through the Unit Commercialization Non-Transportation (KNA) in Operational Area 6 Yogyakarta. Direct marketing is conducted through various media such as direct mail, internet amd telemarketing. This study examines how direct marketing strategies can increase the leasing of non-transportation assets such as kiosks, company-owned houses, and commercial spaces owned by PT Kereta Api Indonesia (Persero). The results show that the implementation of direct marketing is effective in increasing non-transportation revenues and expanding market reach, particularly through targeted direct mail and digital promotion via websites and social media. Challenges include the suboptimal intensity of promotion and the need to enhance the use of various marketing channels. This research highlights the importance of personalization and market segmentation in direct marketing strategies, as well as the significant impact of digital media in promoting the company’s non-transportation assets.